Fabrication of controlled magnet based microparticles on a microfluidic platform - Oh, Teck Min (2016)
Droplet microfluidics is a multidisciplinary platform useful to investigate basic physics, synthesis of novel materials and a range of biomedical applications. Fabrication of Janus structures containing two or more phases in a single (symmetric or asymmetric) particles was realized with droplet microfluidics, utilized for the detection of DNA, proteins and cell encapsulations. If one constitute phase is magnetic, then wireless manipulation capabilities can be realized on droplet microfluidic platform.